INVESTIGATING STMT (SEKOLAH TINGGI MANAJEMEN TRANSPORTASI) STUDENTSâ ATTITUDES TOWARDS LEARNING ENGLISH FOR TRANSPORTATION AND LOGISTIC - Susanthi, Novi Indah; Indraning Tiyas, Yanu Rarasati; Fadiah, Siti (STKIP Bina Bangsa Getsempena Banda Aceh, 2018)
AbstractThe positive attitudes are expected from students when they are learning English. These positive attitudes will help them to get the benefit of learning the language easily and smoothly. When students have positive attitudes meaning that they are at ease to learn and accept the material from the lecturer. This is important since learning process takes place when they are at ease. On the other hand, if students already perform negative attitude towards the language, they will stuck with the barrier, the difficulties to master the language. Consequently, students are de-motivated in mastering the language. For this reason, teaching learning process in the class is not optimum. If this is happen, students do not learn the language at their best. Hence, they are not capable to learn the material that they need to master. Language mastery, in the future, will help them to be able to cope with the language related to their career or job. This study is aimed to find out whether there is a relation between their attitude towards English learning and the mastery of English in their work field. The students are asked to fill in the questionnare and the researchers are observing the studentsâ attitudes in the classrooms when they are studying. The implication of this study is to influence the studentsâ attitude in the teaching learning process. Therefore, the result reveals that the participants indicate some negative attitude towards learning English.Â Keywords: Positive attitudes, learning English, ESP, Transportation and Logistics,Â Â Â Â Â Â STMT Trisakti